2020
DOI: 10.1016/j.mehy.2020.109904
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal proteins as a possible tool for blocking SARS-COV 2 virus replication for a potential prospective treatment

Abstract: Highlights Covid 19 represents a threat for the humanity so there is a dire need to produce a treatment or a protocol to avoid its spread. Ribosomal proteins may resemble an effective tool for attenuation of viral replication. RPL9 can be over expressed and purified from bacteria, yeast and humans. More clinical and cytotoxicity studies are needed to produce an effective and reliable treatment to this pandemic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Hence it has been proposed that ribosomal proteins can be targeted for vaccine candidates. 59 Consequently, we performed a drug repurposing analysis to find drugs that can reverse the altered effect of these proteins. The results of this analysis showed that most of the drugs identified exert antiviral activity.…”
Section: Resultsmentioning
confidence: 99%
“…Hence it has been proposed that ribosomal proteins can be targeted for vaccine candidates. 59 Consequently, we performed a drug repurposing analysis to find drugs that can reverse the altered effect of these proteins. The results of this analysis showed that most of the drugs identified exert antiviral activity.…”
Section: Resultsmentioning
confidence: 99%
“…Enriched genes such as GBP1 [ Niu et al, 2016 ], USP18 [ Xu et al, 2012 ] and OASL (2′-5′-oligoadenylate synthetase like) [ B. Wang et al, 2018 ] were associated with progression of porcine reproductive and respiratory syndrome viral infection, but these genes may be liable for advancement of SARS-CoV-2 infection. Enriched genes such as STAT1 [ Claverie, 2020 ], P2RX7 [ Di Virgilio et al, 2020 ], TLR4 [ Choudhury and Mukherjee, 2020 ], CCR5 [ Patterson et al, 2020 ], CCL5 [ Patterson et al, 2020 ], JAK2 [ Wu and Yang, 2020 ], IFITM3 [ Hachim et al, 2020 ], TLR7 [ Moreno-Eutimio et al, 2020 ], TLR1 [ Choudhury and Mukherjee, 2020 ], TLR2 [ Choudhury and Mukherjee, 2020 ], RPL9 [ Rofeal and El-Malek, 2020 ] and GPX1 [ Seale et al, 2020 ] were involved in progression of SARS-CoV-2 infection. OAS1 was liable for progression of severe acute respiratory syndrome (SARS) viral infection [ Hamano et al, 2005 ], but this gene may be associated with development of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of ribosomal proteins and viral mRNAs were involved in viral protein biosynthesis, and these proteins were important for viral replication and infection of host cells. RPL 9 and RPL 10 could be used to assess the activity of Covid-19 and even became targets for the development of Covid-19 vaccines and treatments ( 38 ).…”
Section: Discussionmentioning
confidence: 99%